2016
DOI: 10.1155/2016/6939018
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Response ofIn VivoHuman Skin to Fractional Radiofrequency Microneedle Device

Abstract: Background. Fractional radiofrequency microneedle system (FRMS) is a novel fractional skin resurfacing system. Data on thermal response to this fractional resurfacing technique is limited. Objectives. To investigate histologic response of in vivo human skin to varying energy settings and pulse stacking of a FRMS in dark-skinned subjects. Methods. Two female volunteers who were scheduled for abdominoplasty received treatment with a FRMS with varying energy settings at 6 time periods including 3 months, 1 month,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Energy-and laser-based therapies such as radiofrequency microneedling, fractional non-ablative laser and fractional ablative laser, all induce broad destruction of tissue, including the destruction of cells containing oxidatively damaged DNA and proteins. While the level of oxidative damage post-treatment has not been specifically tested, these treatments are shown to induce the expression of specific heat shock proteins known to promote the clearance of damaged proteins [61][62][63] .…”
Section: Targeting the Primary Hallmarks Of Agingmentioning
confidence: 99%
“…Energy-and laser-based therapies such as radiofrequency microneedling, fractional non-ablative laser and fractional ablative laser, all induce broad destruction of tissue, including the destruction of cells containing oxidatively damaged DNA and proteins. While the level of oxidative damage post-treatment has not been specifically tested, these treatments are shown to induce the expression of specific heat shock proteins known to promote the clearance of damaged proteins [61][62][63] .…”
Section: Targeting the Primary Hallmarks Of Agingmentioning
confidence: 99%
“…2,45 At day 7, HSP47 and HSP70 are expressed inside the treatment zone as well as more diffusely throughout the dermis. 45 NAFL and fractional radiofrequency microneedling have both been reported to induce HSP70 expression, 46,47 which is severely attenuated in diabetic skin, 48 with an expression time course that correlates with delayed healing. 49 Long-term upregulation of HSPs has been reported after large-area ablative laser resurfacing.…”
Section: Mechanismsmentioning
confidence: 99%
“…Melanin is not a target of FRFM devices and thus people of color can successfully be treated in general [49]. Manuskiatti et al [50] found histologic evidence of neocollagenesis with a single FRFM session in 2 darker skinned women at minimal energy level of 50 Watts; though there was also histologic evidence of hyperpigmentation at their highest energy setting of 80 watts [48]. Two studies on FRFM in Asian patients with acne scars FST III-V demonstrate improvement in scarring based on blinded investigator assessment with transient adverse effects including erythema and edema [51,52].…”
Section: Fractional Resurfacingmentioning
confidence: 99%